Using Fourier Analysis for Torque Estimation of Two-Phase Induction Motor Supplied by Halfbridge Inverter with PWM Control - Zaskalicky, Pavel; Schreier, Ludek (Communications - Scientific letters of the University of Zilina, 2013)
The paper deals with the steady state analysis of electromagnetic torque ripples of a two-phase induction machine, which is supplied by a half-bridge connected inverter with IGBT transistors. The inverter output voltage is controlled by a PWM of the input DC voltage. The complex Fourier series analysis of the inverter output voltage was made to obtain the spectrum of voltage-supply harmonics. Particular voltage harmonics were applied to the two-phase induction machine numerical model so that the electromagnetic torque waveforms for various operation conditions were obtained.